Two new species of Andinopanurgus (Hymenoptera: Andrenidae: Panurginae), with a description of the female of A. amyae - Packer, Laurence (Journal of Melittology, 2021)
Two new species of Andinopanurgus Gonzalez & Engel are described: Andinopanurgus chirosimpson Packer, new species, from northwest Argentina extends the range of the genus south by more than 2000 km and A. lynnae Packer, new species, from Peru. The new species seem to belong to Gonzalez & Engel’s “guarnensis species group” but differ from it in the highly modified setae on S4, which are divided into two to four branches (in A. chirosimpson, the four-branched ones of which look like a thumbless hand and are the source of the specific epithet) to two to five branches (in A. lynnae). The female of A. amyae (Gonzalez & Engel) is described for the first time.